Exploring the effects of cognitive remediation on metacognition in people with schizophrenia - Matteo Cella; Clementine Edwards; Sarah Swan; Kay Elliot; Clare Reeder; Til Wykes (Journal of Experimental Psychopathology, 2019)
Background: Interventions targeting cognition in people with schizophrenia have shown moderate effects on improving functioning. Recent cognitive remediation (CR) approaches have begun to target metacognition to improve functioning outcomes. This study aims to develop a novel measure of metacognition and assess whether metacognitive-based CR (mCR) can improve metacognition. Method: We use data from a single-blinded randomized controlled trial comparing mCR plus treatment as usual (TAU) to TAU alone in people with schizophrenia. Participants were assessed with measures of cognition, functioning, and a new measure of metacognition at three time points: Week 0 (baseline), Week 12, and Week 24. Results: The evaluation of the novel metacognition assessment suggests that it is a reliable and valid measure. The measure positively correlates with cognitive measures, in particular with executive function and IQ but also with a measure of functioning. We found that a course of mCR was able to increase metacognition compared to TAU by Week 24. Conclusions: Metacognition may be an important mechanism to explain how CR affects functioning outcomes in people with psychosis. The systematic assessment of metacognition as part of CR studies may help to evaluate more clearly its role and relevance to functioning.